Polyculture Engineering of White Shrimp Vannamei and Seaweed on Different Planting Distance on The Growth, Survival in Abration Pond - Istiyanto Samidjan; Diana Rachmawati (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
The objective of the study was to assess the role of polyculture engineering of vanamei shrimp, and seaweed in an effort to increase growth and survival. The experimental method was randomized complete design with 4 treatments and 3 replications were T1 (10 PL / m2 white shrimp vannamei and seaweed distance 15 cm), T2 (10 PL / m2 of white shrimp vannamei and seaweed distance 30 cm), T3 (10 PL / m2 white shrimp vanamei and seaweed distance 45 cm, T4 (10 PL / m2 white shrimp vanamei and seaweed 60 cm). Seaweed used Gracillaria sp type 150 g / bundle with treatment used a long line system placed around the nets plot of 1 m2 in pond culture 300 m2. Data includes the growth of absolute weight, survival, FCR were analyzed variety and test Tukey. observation of the water quality of maintenance media include nitrite, ammonia, temperature, pH, salinity using descriptive. There is a very real effect (P <0.01) on treatment with different plant spacing on seaweed and vanamei shrimp on growth and survival of white shrimp vanamei and seaweed. The highest absolute weight growth in vanamei shrimp was T4 treatment (vanamei shrimp 29.25 ± 0.07 g), and seaweed (2919.03 ± 8.70bg) of white shrimp vanamei survival rate (98.25% ± 2.25%) and FCR (food Conversion ratio) 1.15 ± 0.09. Water quality is still feasible optimum.